(untitled) (International Journal of Engineering and Computer Science, 2017)
Information technology has a huge role in today’s life. Development of Information Technology will be used by the users to help with the work. Application of Information Technology in education is to have good aim, in the world of information technology education can help all the activities and the learning process can also generate reports very quickly. This study focused on the development models of monitoring parents to students results. In this research method used is OOAD (Object Oriented Analysis Design). The results of the research that has been done is to help the process of monitoring the learning process effective and efficien.